The Posthumous Life of Dr. Mabuse - Kłys, Tomasz (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
Dr. Mabuse, master of crime and No.1 enemy of society, was invented as fictional character by Luxembourgian writer Norbert Jacques in his novel from 1921. Char-acter of Mabuse inspired great German director Fritz Lang to make three films. In the first one, Dr. Mabuse, der Spieler (1922), he is powerful criminal figure, de-stroying social and economic life of young Weimar Republic and could be per-ceived as an allegory of German inflation at the beginning of 1920-s. Caught, how-ever, by general attorney Von Wenk, in the final of film is placed in psychiatric asylum. In Lang’s sequel Das Testament des Dr. Mabuse (1933) Mabuse in the halfof film dies as physical person in psychiatric clinic of Professor Baum. However, hebecomes by fact of his death the more dangerous as immaterial and abstract Idea ofEvil which could be incarnated in everyone. The third and last Lang’s Mabuse film,Die 1000 Augen des Dr. Mabuse (1960) is at the same time the first one of Mabuseseries produced by Arthur Brauner for his Berlin company CCC-Filmkunst.Brauner’s series consists of 7 films (including Lang’s last work) made in the decade1960–1970. The short analysis of it is made on the base of powerful monographyThe Strange Case of Dr. Mabuse by American film historian David Kalat who is alsoeditor of DVD edition of Brauner’s series.